Integrated disease management of potato in the northeastern Himalayan region of India - Gurjar, Malkhan Singh; Sharma, Sanjeev; Sagar, Vinay; Bag, T K (Indian Farming, 2019)
Potato (Solanum tuberosum L.) is an important crop after rice and wheat is being grown worldwide. India is second largest producer of potato in the world after China. Potato is also a staple crop of the north eastern Himalayan region of India contributing nearly 10% of the country’s total potato area. The main reasons for the low productivity are inadequate availability of healthy seed potato vis-a-vis poor management practices and presence of economically important diseases, viz. late blight, bacterial wilt/brown rot etc. More than 150 potato diseases caused by fungi, bacteria, viruses and physiological disorders are known throughout the world. In the north eastern Himalayan region, foliar diseases are predominant like late blight, early blight and leaf spots but soil and tuber borne diseases are also present in very low incidence, viz. bacterial wilt/ brown rot, common scab of potato.